Hypersexuality associated to pramipexole in the treatment of parkinsonian symptoms: presentation of 3 cases and review of the literature - Custodio, Nilton (2010)
Introduction: Impulse control disorders have been reported in patients with Parkinson’s disease (PD), and in users of dopamine agonists. We report three cases of patients with parkinsonian symptoms and hypersexuality, an impulse control disorder associated with pramipexole use. Case reports: Case 1: A 62-year-old man with PD treated with levodopa/carbidopa. He needed to start pramipexole and twelve months later he presented hypersexuality that improved with escitalopram. Case 2: A 66-year-old man with PD treated with levodopa/carbidopa, entacapone and clonazepam. He needed to start pramipexole; sixteen months later he presented hypersexuality that disappeared with escitalopram. Case 3: A 45-year-old man with Parkinsonism secondary to acute disseminated encephalomyelitis treated with risperidone, amitriptyline and clonazepam. He needed to start pramipexole; two months later, he presented hypersexuality and received escitalopram; hypersexuality disappeared only when decreasing pramipexole dose; then he started levodopa/carbidopa and hypersexuality reappeared that decreased again when reducing levodopa/carbidopa dose. Conclusions: Pramipexole may be associated with hypersexuality, but it is necessary to be careful with characteristics either related to disease or to individual factors. Hypersexuality may improve with escitalopram and its associated symptoms should be treated.